Ultrasensitive Prostate Specific Antigen Immunosensor Based on Gold Nanoparticles Functionalized Polypyrrole@Carbon Nanotubes - Zou, Y.J.; Xiang, C.L.; Sun*, L.X.; Xu, F.; Zhou, H.Y. (Asian Journal of Chemistry, 2014)
In this paper, an ultrasensitive electrochemical immunosensor for the detection of prostate specific antigen (PSA) based on gold nanoparticles functionalized polypyrrole@carbon nanotubes nanocomposite was reported. Pyrrole monomer was polymerized on MWNTs substrate in acid solution. Negatively charged gold nanoparticles (AuNPs) were assembled on the PPy@MWNTs by electrostatic interactions. With the primary antibody (Ab1) immobilized on the AuNPs/PPy@MWNTs nanocomposite, a sandwich electrochemical immunosensor for the detection of prostate specific antigen was constructed. The electrochemical signal was amplified substantially by the nanocomposite. A wide linear range from 0.002 to 20 ng mL-1 with a detection limit of 0.001 ng mL-1 (the ratio of signal to noise, S/N = 3:1) was obtained, which is comparable or even better than most of the prostate specific antigen immunosensor. Furthermore, the prepared immunosensor showed excellent selectivity and reproducibility.